A new species in the genus Chroogomphus (Gomphidiaceae) from India - Das, Kanad; Vizzini, Alfredo; Parihar, Arvind; Hembrom, Manoj E.; Ghosh, Aniket (Phytotaxa, 2021)
Chroogomphus himalayanus sp. nov. is described from the subalpine Himalaya region of India. It is presented herein with morphological descriptions, illustrations and nrITS-based phylogenetic inferences as well as comparisons with similar species.